Did Christ die only for the Elect?: Limited Atonement vs. Unlimited Atonement - Isaac Boaheng (International Journal of Social Science and Religion (IJSSR), 2023)
Almost all Christians believe that the satisfaction rendered by the death of Christ was in itself enough for the salvation of humanity. Yet, there is no consensus among Christians on the question of the beneficiaries of Christ’s atoning sacrifice. The question of whether Christ’s suffering and death benefited all humanity or only an elected few has triggered much debate among Christian scholars. The different responses to the question of the extent of the atonement can be categorized broadly into two, namely; particular atonement (that is, the view that Jesus Christ died only for the elect) and universal atonement (that is, the idea that Christ died for all persons). The significance of the debate and the rise in interest in this subject in recent times has prompted this literature-based research which critically reviews and analyzes publications (including books, journal articles, and dissertations) on the extent of Christ’s atonement to see how one might make meaning of the ongoing debate. The paper first presents a survey of the evidence adduced for both views; it then considers Calvin’s view on the subject and ends with the author’s position that the atonement is unlimited in scope in that the offer of salvation is for all people; yet it is limited in effect because only those who believe in Jesus are truly saved.